Impaired response to hypoxia in the respiratory center is a major cause of neonatal death of the PACAP‐knockout mouse. Issue 3 (9th November 2012) - Arata, Satoru; Nakamachi, Tomoya; Onimaru, Hiroshi; Hashimoto, Hitoshi; Shioda, Seiji
Abstract Pituitary adenylate cyclase‐activating polypeptide (PACAP) is a neuropeptide expressed widely in nervous tissues. PACAP‐knockout (−/−) mice display a sudden infant death syndrome (SIDS)‐like phenotype, although the underlying physiological mechanism to explain this remains unclear. Here, we report on the presence of abnormal respiratory activity in PACAP−/− mice under hypoxic conditions, which provides a basis for the SIDS‐like phenotype. PACAP−/− mice display a lowered baseline respiratory activity compared with wild‐type animals, and an abnormal response to hypoxia. More specifically, PACAP−/− mice at postnatal day 7 showed respiratory arrest in response to hypoxia. In contrast, their response to hypercapnic conditions was the same as that of wild‐type mice. Histological and real‐time PCR analyses indicated that the catecholaminergic system in the medulla oblongata was impaired in PACAP−/− mice, suggesting that endogenous PACAP affects respiratory centers in the medulla oblongata via its action on the catecholaminergic system. We propose that disruption of this system is involved in the SIDS‐like phenotype of PACAP−/− mice. Thus, disorders of the catecholaminergic system involved with O2 sensing could be implicated in underlying neuronal mechanisms responsible for SIDS.